Coastal Ecosystems :Hazards, Management and Rehabilitation - Datta,Rattan K (Centre for Science & Technology of the Non-Aligned and Other Developing Countries (NAM S & T Centre) : Daya Pub. House, 2008)
Transcript of papers presented during an international workshop-cum-training programme organized at Purwokerto, Indonesia during August 2006 by the Centre for Science & Technology of the Non-Aligned and Other Developing Countries in collaboration with the Centre for Tropical Marine Ecology, Bremen, Germany and Jenderal Soedirman University of Indonesia.